Análisis del Perfil del Turista en la Parroquia Urbana Zaruma, Patrimonio Cultural y Pueblo Mágico del Ecuador - Zeas Macas., Yomara Lissbeth (2022)
The urban parish of Zaruma has a considerable tourist demand thanks to its cultural tourism offer, but lacks information on the profile of the tourists who visit it. Therefore, the main objective of this research is to analyze the profile of tourists visiting the urban parish of the Zaruma canton, thus, three specific objectives were proposed. For the first objective, the methodology of Tourism Diagnosis of Communities used by Carla Ricaurte Quijano was used, as well as the data sheet of tourist attractions created by the Ministry of Tourism in 2018, which it provided information on the current situation of the six elements that make up the tourism system and the updating of the inventory of 17 tourist attractions, which 82% corresponds to hierarchy III and the remaining 18% to hierarchy II. For the second objective, the methodology of the Centro de Estudios Superiores en Turismo CESTUR was used, which proposes several points: the sociodemographic profile of visitors, the structure of consumption of tourist goods and services, the organization of the trip and motivational variables. The results determined that exists a greater presence of national tourists who come mainly from provinces such as Guayas, El Oro and Pichincha; whose daily tourist expenditure is mainly for food and beverages, and finally, their reasons for visiting are related to the cultural tourism offer. Based on the results of the tourist profile and their motivations, the third objective was fulfilled through a market segmentation and proposal of the "Sarahuma" Tourist Route that was made with a focus on a cultural product line, this route has a duration of 2 days - 1 night and was included in a tourist package.